Psychological characteristics of developing excellence in elite youth football players in English professional academies - Saward, C.; Morris, J. G.; Nevill, M. E.; Minniti, A. M.; Sunderland, C. (Journal of Sports Sciences, 2020)
This mixed-longitudinal prospective study examined the development of psychological characteristics of developing excellence in relation to the career progression of elite youth football players. In a 20-month period, 111 academy football players aged 11-16 completed the Psychological Characteristics of Developing Excellence Questionnaire (PCDEQ) on 1-5 occasions. This combination of single and repeated assessments resulted in a mixed-longitudinal sample of 226 completed PCDEQs. Players were then prospectively tracked, and their scholarship status assessed at follow-up, at age U17. Multilevel modelling revealed that coping with performance and developmental pressures scores increased with age, and that Category 1-2 academy scholars (4.35 ± 0.61) scored higher than Category 3-4 academy scholars (3.99 ± 0.67) and non-scholars (4.02 ± 0.78) (p < .05). Evaluating performances and working on weaknesses scores increased with age for Category 1-2 academy scholars (U12-U14 vs. U15-U16 = 5.16 ± 0.48 vs. 5.38 ± 0.45), compared to non-scholars (U12-U14 vs. U15-U16 = 5.11 ± 0.59 vs. 5.03 ± 0.71) (p < .05). Imagery use during practice and competition scores decreased with age (U12-U14 vs. U15-U16 = 4.45 ± 0.66 vs. 4.29 ± 0.70) (p < .05). A blend of PCDEs may facilitate optimal career progression. Football academies should develop players` PCDEs, with a particular focus on developing their coping skills and their ability to realistically evaluate performances and work on weaknesses.